Participatory Oversight Strategy of the Lampung Provincial Election Supervisory Agency in Preventing Violations in the 2024 Elections - Ahmad Qohar; Anna Gustina Zainal; Dedy Hermawan; Nur Efendi (Utan Kayu Publishing, 2026)
Indications of money politics, violations of civil servant neutrality, and intimidation of voters were found in various regions. This shows that participatory oversight is not yet fully optimal. Based on findings in the field, money politics is still rampant ahead of election day san. The methods are increasingly varied, such as the distribution of basic foodstuffs, digital transfers, and program promises. Many citizens still consider this to be